Atlas morphometry: A radiologic- Anatomical study - S R Jyothi; Joish Upendra Kumar; Preetam Patil; S R Vinay (Wolters Kluwer Medknow Publications, 2024)
Introduction: Atlas is an atypical cervical vertebra with unique anatomy and related to many vital structures. Any surgical intervention at this level, especially transpedicular and transarticular screw placement, requires in detail assessment of the structure of the atlas. Certain measurements considered surgically important were measured on computerized tomography (CT) scans and compared with corresponding measurements on dry bones. Methodology: The study was carried out in KVG Medical College and Hospital, Sullia, including 100 CT scans of 43 females and 57 males with a mean age of 31.4 years and 40 dried atlas vertebrae available in the Department of Anatomy. Lengths and widths of superior and inferior articular facets were measured on both CT scans and dry bones and compared. Length, width, and heights of lateral masses, along with height below the posterior arch (HBPA), maximum medialization and cranialization angles were assessed on CT scans. The mean, standard deviation, and significance of differences were calculated using an independent t-test. Results: Mean value and standard deviation were calculated for the measured parameters. Superior and inferior facet measurements were compared between CT scan images and dry bones and no significant difference was found. Conclusion: Morphometric measurements of atlas on CT images are useful for planning of screw fixation surgeries, particularly to avoid injury to vital structures. Values of measurements, especially maximum medialization angle, maximum cranialization angle, and HBPA, are in agreement with other studies and are proposed to be included as part of preoperative workup.